Pengaruh Efikasi Diri dan Kemandirian Belajar Terhadap Pemahaman Konsep Ilmu Pengetahuan Alam pada SMP Negeri di Kabupaten Bekasi - Alber Ashari, Achmad; Suendarti, Mamik; Dasmin, Adi (ALFARISI: Jurnal Pendidikan MIPA, 2026)
The purpose of this research is to find out. 1) The effects of self efficacy and learning independence jointly towards the understanding of natural science concepts of public junior high school students in Bekasi district. 2). The effect of self efficacy towards the understanding of natural science concepts of public junior high school students in Bekasi district. 3). The effect of learning independence towards the understanding of natural science concepts of public junior high school students in Bekasi district. The methode used in this study is a survey with multiple linier regression correlational techniques with a sample of 86 students. The results of the study show: 1) There are significant effects of self efficacy and learning independence jointly towards the understanding of natural science concepts of public junior high school students in Bekasi district. This isevidenced by the acquisition of the value of Sig = 0.000 < 0.05 and Fcount = 47,969. 2). There is a significant effect of self efficacy towards the understanding of natural science concepts of public junior high school students in Bekasi district. This is evidenced by the acquisition of thevalue of Sig = 0.000 < 0.05 and tcount = 5,641. 3).There is a significant effect of learning independence towards the understanding of natural science concepts of public junior high school students in Bekasi district. This is evidenced by the acquisition of the value of Sig. 0,008 < 0,05 dan thitung = 2,736.